Associations between platelet indices and cerebrospinal fluid biomarkers of Alzheimer’s disease pathology in cognitively intact adults: the CABLE study - Shi-Yin Xiong; Yong-Li Zhao; Yan Fu; Qiong-Yao Li; Quan Hao; Dan-Dan Zhang; Min Liu; Shan Yin; Lan-Yang Wang; Yong-Chang Wang; Shu-Dong Qiu; Zi-Qi Zhang; et al. (Alzheimer’s Research & Therapy)
Abstract Introduction Although previous studies have shown that specific platelet indices had correlations with cognitive impairment, the associations between platelet indices and cerebrospinal fluid (CSF) biomarkers of Alzheimer’s disease (AD) pathology remain unclear. Methods Our study included 1,047 cognitively normal participants from the Chinese Alzheimer's Biomarker and LifestylE (CABLE) study. The total participants had an average age of 58.33 years, a female proportion of 41.5% and average educational attainment of 9.58 years. Multiple linear regression models were used to analyze the associations of five platelet indices (plateletcrit [PCT], platelet count [PLT], mean platelet volume [MPV], platelet distribution width [PDW], and platelet large cell ratio [PLCR]) with CSF AD biomarkers after adjusting for age, gender, education and APOE ε4 allele status. Furthermore, the interactive, stratified and sensitivity analyses were further conducted to verify their relationships. Results In the total participants, we found higher PCT levels were significantly correlated with higher CSF P-tau/Aβ42 (β = 0.102, P = 0.008) and T-tau/Aβ42 (β = 0.102, P = 0.008), as well as lower CSF Aβ42 (β = -0.089, P = 0.018) and Aβ42/Aβ40 (β = -0.093, P = 0.018). Moreover, other four platelet indices (PLT, MPV, PDW, PLCR) demonstrated moderate correlations with CSF AD biomarkers. The interaction analyses revealed that age affected the correlations between PCT and PLT with CSF Aβ42. Importantly, the associations between PCT and the aforementioned CSF AD biomarkers became more significant in the late-life group, but turned non-significant in the mid-life group. Besides, sensitivity analyses confirmed the robustness of our findings. Conclusions Our study provided preliminary evidence suggesting potential associations between platelet indices (especially PCT) and CSF AD biomarkers in cognitively intact adults. Nonetheless, more studies are needed to further validate these findings.